Rights remembered : a Salish grandmother speaks on American Indian history and the future - Hillaire, Pauline, 1929- (American Indian lives., 2016)
"An autobiography of a contemporary Native American woman that combines her own life experiences, tribal oral traditions, and the written record of relationships between the United States and the native peoples of the Northwest Coast to provide a Native view of recent history"--Provided by publisher.